Peer effects in active learning - Lima, Vinicius Gomes de (2017)
This paper investigates peer effects in higher education in an environment of active learning that gives great importance for students’ interaction through group work. Our empirical strategy uses exogenous variation in group composition to estimate peer effects in different exercises. We find no evidence of peer effects in a basic linear-in-means specification considering all assigned peers. However, we find positive and statistically significant impact of peers coming from student’s same high school. We also find no evidence of peer effects with a model that takes into account student and peers’ position in the ability distribution.